The Effect of a Distributed Virtual Reality Simulation Training Program on Dissection Mastoidectomy Performance - Andersen, Steven Arild Wuyts; Foghsgaard, Søren; Cayé-Thomasen, Per; Sørensen, Mads Sølvsten (Otology & neurotology, 2018)
To investigate the effect on final-product performance of a distributed, virtual reality (VR) simulation training program on cadaveric dissection performance and learning curves compared with standard VR simulation training during a temporal bone course. Educational interventional cohort study. The national Danish temporal bone courses of 2016 and 2017. Postgraduate year 2 to 5 residents in otorhinolaryngology. Nine participants volunteered for additional VR simulation training (intervention) before the temporal bone course, with training blocks distributed (i.e., separated). The remaining 28 participants received standard VR simulation training during the temporal bone course (control). VR simulation and cadaveric dissection final-product performances were analyzed by blinded raters using a 26-item modified Welling Scale. Distributed VR simulation training before the temporal bone course (intervention) significantly increased dissection final-product performance by 25% compared with standard VR simulation training during the course (control) (mean scores 12.8 points versus 10.3 points, p < 0.01). Distributed and repeated VR simulation practice markedly decreased drilling time. Guidance by the simulator-integrated tutor-function significantly increased final-product performance by 2.3 points compared with nontutored procedures but at the cost of increased drilling time. Skills acquired in a VR simulation environment translate to cadaveric dissection skills and repeated and distributed VR simulation can be used to further increase performance compared with standard VR simulation training during a temporal bone course. Further dissemination of inexpensive VR simulators would allow all future temporal bone course participants to train locally before attending future centralized courses.